Substitusi Tepung Rumput Laut Eucheuma striatum pada Pakan Ikan Nila (Oreochromis niloticus) - Alamanda Juwita Putri; Salnida Yuniarti Lumbessy; Dewi Putri Lestari (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2021)
Feed is one of the most influential factors on the appearance of tilapia productivity. This study aimed to analyze the effect of substitution of fish feed with Eucheuma striatum seaweed meal on the cultivation of Tilapia (Oreochromis. niloticus). This research was conducted at the Laboratory of Aquaculture Study Program, Faculty of Agriculture, Mataram University. The method used in this study was a completely randomized design (CRD), which consisted of 4 treatments with 3 replications, ie: control (P1), concentration of 4% seaweed flour (P2), concentration of 8% seaweed flour (P3), and concentration of 12% seaweed flour (P4). The results showed that substitution of fish feed with seaweed meal E. striatum could affect growth and specific growth rate, but did not affect Feed Utilization Efficiency (EPP), Feed Conversion Ratio (FCR), and Survival Rate (SR) of Tilapia. Fortification of E. striatum flour at concentrations of 4% and 8% in feed gave better absolute and specific weight growth of Tilapia, while the best absolute length growth was found in the addition of 8% E. striatum flour, which was 2.26 cm.